CULTIVATION OF STRAW MUSHROOMS USING CORN COB WASTE TO INCREASE SELF-RELIANCE OF YOUTH ORGANIZATIONS IN DESA TOLO'OI, SUMBAWA - Lukman Azis (Pusat Pengembangan dan Kajian Sarana dan Prasarana Pendidikan (P2K Sarprasdik), 2022)
Corn cob is one of agricultural wastes that have not been used optimally by the community, especially in Desa Tolo'Oi, Kabupaten Sumbawa. The aim of Pengabdian kepada Masyarakat (PkM) was to improve the ability on using corncob waste as straw mushroom cultivation media interm of a way to increase self-reliance of youth organization in Desa Tolo'Oi. A total of 25 youth Karang Taruna desa Tolo'Oi were participated in this PkM. This PkM used a demonstration method while the pre- and post-test methods were used to measure the increasing of participants knowledges. The implementation of this PkM included several stages, namely (1) Processing of corncob waste as mushroom cultivation media; (2) Caring, watering and post-harvest; (3) Processing of mushroom, (4) Packaging and labeling of food products and; (5) Digital marketing training. The results of PkM show that all participants were increasingly aware of the existence and the dangers of corncob waste. 100% have also understood to cultivate, harvest and make processed mushroom products. Not only that, 80% of participants also knew the types, benefits of packaging and labels as one of the attractions and strategies for selling food products. However, only 92% and 85% of participants understood the benefits of corncob waste and marketing strategies through digital marketplaces. In conclusion, 100% of participants increased their knowledge in cultivation practices of straw mashroom also the digital marketing.